Injury risk in elite young male soccer players: a review on the impact of growth, maturation, and workload - Ribeiro, N.; Martinho, D. V.; Pereira, J. R.; Rebelo, A.; Monasterio, X.; Gonzalo-Skok, O.; Valente-dos-Santos, J.; Tavares, F. (The Journal of Strength and Conditioning Research, 2024)
The long-term development of young male soccer players involves a prolonged period of significant adjustments, highlighting the importance of studying the complex interaction between dynamic variables, including workload, and inherent elements like growth and maturity. This analysis examines the intricate connections involving the development, maturity, workload, and susceptibility to injuries among adolescent male soccer players. Significantly, these connections become prominent at the peak height velocity (PHV) period, a crucial moment in maturation. Growth rates vary among individuals, and higher rates have been associated with an increased risk of injury in young soccer players, particularly during periods of rapid growth. Identifying possible risk factors and understanding the complex connections between them is crucial to developing specific methods for reducing the risk of injury. Sharing this valuable information with essential stakeholders is crucial for guaranteeing young athletes' comprehensive growth and maturation process. Furthermore, this review emphasizes the immediate need for long-term studies and thorough injury analyses to comprehend better the dynamic interactions that influence injury patterns in young male soccer players. This review will allow practitioners to better understand the main modifiable and nonmodifiable risk factors for injury and provide essential information focusing on practical strategies, facilitating more informed decision making by all stakeholders. The review aims to clarify these complexities and offer crucial insights that can assist in designing and implementing efficient strategies to reduce the risk of injury, specifically for the challenges faced during PHV and within the broader framework of long-term athletic development in young soccer.